Lordless! - Margit Ernst-Habib (Pistis & Praxis: Teologia e Pastoral, 2022)
Re-reading and interpreting Karl Barth’s narrative of the “Lordless Powers” (Church Dogmatics IV/4: Lecture Fragments/The Christian Life) for our contemporary times of crises, the article argues that prayer indeed leads the faithful towards active engagement with the world and, as Barth puts it, towards a revolt against the disorder of the world. The subversive power of prayer arising from the Christian life as a life in prayer is understood here as a guide from contemplation to action, introducing a new realism and establishing a connection between theological insights and political analysis. The good news this subversive power of prayer brings to light is the Gospel news that neither humanity nor creation are forsaken, but that there is “another possibility” given by God, which does not have to be created by humanity, but which humanity can hasten to meet through the work of the Holy Spirit.